2002
DOI: 10.1248/jhs.48.83
|View full text |Cite
|
Sign up to set email alerts
|

Problems with Methods used to Screen Estrogenic Chemicals by Yeast Two-Hybrid Assays.

Abstract: We developed a yeast two-hybrid assay using a human-type estrogen receptor (hERα) to screen test chemicals reporting weak estrogenic activity at high concentrations. As a result of exposure to several test chemicals, viable yeast cells showed a decrease in number compared with a control. It was shown that this phenomenon was due to fungicidal effects of the test chemicals within the yeast cell or to inhibition of yeast cell proliferation. Therefore, in performing a yeast twohybrid assay, it is necessary to mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Examples are given in Table 1. The cells are transformed (or transfected) by introducing vectors bearing DNA sequences for human or mammalian nuclear ERs, in conjunction with the appropriate response elements, promoter region and reporter gene. Some potential problems with yeast-based systems include: effects on assay system of test materials that have fungicidal activity or inhibit cell proliferation, solubility, permeability or transport issues due to such things as presence of a cell wall (ICCVAM, 2003), molecular size, or molecular structure, and the potential confounding activity of endogenously produced metabolites or the failure of the yeast system to metabolise test material (Nakano, et al, 2002). Work to overcome some of these potential problems, to optimise yeast assays has been recently published.…”
Section: In Vitro Functional Tests: Transactivation Assays (Hormone-smentioning
confidence: 99%
“…Examples are given in Table 1. The cells are transformed (or transfected) by introducing vectors bearing DNA sequences for human or mammalian nuclear ERs, in conjunction with the appropriate response elements, promoter region and reporter gene. Some potential problems with yeast-based systems include: effects on assay system of test materials that have fungicidal activity or inhibit cell proliferation, solubility, permeability or transport issues due to such things as presence of a cell wall (ICCVAM, 2003), molecular size, or molecular structure, and the potential confounding activity of endogenously produced metabolites or the failure of the yeast system to metabolise test material (Nakano, et al, 2002). Work to overcome some of these potential problems, to optimise yeast assays has been recently published.…”
Section: In Vitro Functional Tests: Transactivation Assays (Hormone-smentioning
confidence: 99%
“…Some potential problems with yeast-based systems include: effects on assay system of test materials that have fungicidal activity or inhibit cell proliferation, solubility, permeability or transport issues due to such things as presence of a cell wall [67]; molecular size, or molecular structure; and the potential confounding activity of endogenously produced metabolites or the failure of the yeast system to metabolise test material [74]. Work to overcome some of these potential problems, optimising yeast assays has recently been published.…”
Section: In Vitro Functional Tests: Transactivation Assays (Hormone-smentioning
confidence: 99%
“…However, Ohyama et al (10) reported that high concentrations of certain styrene dimers and trimers showed estrogenic effects in an ER binding assay and in the E-SCREEN assay. Recently, several assay systems have been used to assess endocrine-disrupting effects, but a few of these assay systems can cause false-positive reactions when test compounds are at high concentrations (11).…”
mentioning
confidence: 99%